Sectioning effects of porphyritic chondrules: Implications for the PP/POP/PO classification and correcting modal abundances of mineralogically zoned chondrules. (1st May 2020) - Barosch, Jens; Hezel, Dominik C.; Sawatzki, Lena; Halbauer, Lucia; Marrocchi, Yves
Abstract: Mineralogically zoned chondrules are a common chondrule type in chondrites. They consist of olivine cores, surrounded by low‐Ca pyroxene rims. By serial sectioning porphyritic chondrules from carbonaceous, ordinary, and enstatite chondrites, we demonstrate that the 2‐D textural appearances of these chondrules largely depend on where they are cut. The same chondrule may appear as a porphyritic pyroxene (PP) chondrule when sectioned through the low‐Ca pyroxene rim, and as a porphyritic olivine‐pyroxene (POP) or porphyritic olivine (PO) chondrule when sectioned close or through its equator. Chondrules previously classified into PP/POP/PO chondrules might therefore not represent different types, but various sections through mineralogically zoned chondrules. Classifying chondrule textures into PP, POP, and PO has therefore no unequivocal genetic meaning, it is merely descriptive. Sectioning effects further introduce a systematic bias when determining mineralogically zoned chondrule fractions from 2‐D sections. We determined correction factors to estimate 3‐D mineralogically zoned chondrule fractions when these have been determined in 2‐D sections: 1.24 for carbonaceous chondrites, 1.29 for ordinary chondrites, and 1.62 for enstatite chondrites. Using these factors then shows that mineralogically zoned chondrules are the dominant chondrule type in chondrites with estimated 3‐D fractions of 92% in CC, 52% in OC, and 46% in EC.